CAVERNOUS HEMANGIOMA: A RARE TUMOR IN THE BREAST REGION - Pacheco, Eimi Nascimento; Tiedje, Amanda Roepke; Simezo, Érica Elaine Traebert; Fernandes, Bráulio Leal; Heinzen, Rebeca Neves (Mastology, 2020)
Introduction: Hemangiomas are benign vascular tumors rarely located in the breast (incidence of 0.4% to 0.8%). They mainly affect post-menopause women on hormone replacement therapy (HRT). These tumors are classified as capillary or cavernous according to the size of vessels involved and can show heterogeneity in imaging tests. Case report: The patient is a woman aged 56 years, G3P3, living in the city of Florianópolis. She has been on HRT, without a family history of gynecological cancer. She reported breast implant and bariatric surgery in 2007. The patient sought medical care due to a tumor in the left breast that she noticed six months before, with slight growth. Physical examination identified a superficial purplish nodule in the left axillary tail, measuring 1.5 cm. Magnetic resonance imaging (MRI) revealed an intra-mammary lymph node (BI-RADS 2); mammography (MMG) indicated a 2.4 cm nodule in the left axillary tail (BI-RADS 4), suggesting biopsy; ultrasound (US) identified an irregular peripheral nodule at 2 h on the left, with the same classification. Core biopsy revealed cavernous hemangioma. Mammaplasty was performed with excision of the lesion. Commentaries:In hemangiomas, imaging findings can vary. MMG usually shows an oval or lobular mass, isodense or high-density, and circumscribed margins. The heterogeneity in the US may be related to vascular channels histologically seen in cavernous hemangiomas. MRI characteristics vary according to the possibility of internal thrombosis, but they often include an ovoid mass and circumscribed margins. The MRI report showed no hemangioma; however, MMG and US indicated similar characteristics. Although rare and with a heterogeneous presentation, hemangioma should be remembered as a differential diagnosis since, in addition to its similarities to benign lesions, such as bruises and sebaceous cysts, it can also be mistaken for inflammatory carcinoma and ductal carcinoma in situ, mimics that have been described in the literature.